2023
DOI: 10.1088/1748-9326/ad059c
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the main climatic drivers to the variability of gross primary productivity at global FLUXNET sites

Hao Zhou,
Xu Yue,
Bin Wang
et al.

Abstract: Climate exerts both short-term and long-term impacts on the ecosystem carbon assimilation. However, the main climatic drivers for the variability of gross primary productivity (GPP) remain unclear across various timescales and vegetation types. Here, we combine the state-of-the-art machine learning algorithms with a well-established explanatory method to explore the impacts of climatic factors on long-term GPP variability at global FLUXNET sites across four timescales and six plant functional types. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Our analyses revealed larger increasing rate of GPP than ET in response to diffuse radiation, consistent with previous studies. Wang et al (2023) also found that the GPP of grassland was 1.15 ± 0.16 times higher under diffuse radiation compared to direct radiation, based on flux measurements from global FLUXNET sites. Meanwhile, they observed no significant differences in ET between the two radiation conditions, with a ratio of only 1.00 ± 0.13.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Our analyses revealed larger increasing rate of GPP than ET in response to diffuse radiation, consistent with previous studies. Wang et al (2023) also found that the GPP of grassland was 1.15 ± 0.16 times higher under diffuse radiation compared to direct radiation, based on flux measurements from global FLUXNET sites. Meanwhile, they observed no significant differences in ET between the two radiation conditions, with a ratio of only 1.00 ± 0.13.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…Instead, our analyses suggested that ET responses to K d were nonlinear due to the joint modulation of total PAR. At low to medium PAR levels, ET increased with K d due to the increased plant photosynthesis, which promoted ecosystem transpiration through carbon-water coupling (Strada et al 2015, Wang et al 2023. However, at the high PAR levels, ET decreased with the increase of K d at both sites.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations